Problem Based Learning Model to Improve Students' Conceptual Understanding of Ablution Material at SD Negeri Tenembak Alas - Mardianti (Jurnal Profesi Guru Indonesia, 2024)
This research aims to explore the effectiveness of the Problem Based Learning (PBL) learning model in improving the understanding of class 2B Tenembak Alas Elementary School students on the material of ablution procedures. PBL was chosen because this approach encourages students to actively participate in the learning process and relate knowledge to real situations. Through this approach, it is hoped that students will not only understand the concept of ablution, but also be able to apply it in their daily lives. The research method used is class action with two cycles. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. In its implementation, students are given problems related to ablution procedures that they must discuss and solve in groups. This activity is expected to increase students' curiosity and ability to work together in groups. Data was collected through an initial test and a final test to measure student understanding before and after the application of the PBL model. In addition, observation of student activities is also done to assess the level of engagement and interaction during the learning process. The results of the data analysis show that there is a significant increase in students' understanding of ablution procedures after the application of the PBL model. The average value of students' final test increased compared to the initial test, reflecting a substantial increase in understanding. In addition, observations show that students are more active in participating, asking questions, and discussing during learning. The involvement of students in groups makes them better understand the steps in practical ablution. This research concludes that the Problem Based Learning model is effective in improving students' understanding of ablution procedures. With an interactive and contextual approach, students not only learn theoretically but can also apply that knowledge in everyday life. Therefore, the application of PBL can be an interesting and useful alternative learning strategy in primary schools.